2022
DOI: 10.48550/arxiv.2201.09634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electromagnetic anomaly in the presence of electric and chiral magnetic conductivities in relativistic heavy-ion collisions

Irfan Siddique,
Shanshan Cao,
Uzma Tabassam
et al.

Abstract: We study the spacetime evolution of electric (E) and magnetic (B) fields along with the electromagnetic anomaly (E • B) in the presence of electric (σ) and chiral magnetic (σχ) conductivities in Au+Au collisions at √ sNN = 200 GeV. By comparing to the Lienard-Wiechert solutions with zero conductivities, we observe a symmetry breaking of the electromagnetic field in a conducting medium with respect to the reaction plane. The decay of the field is also significantly decelerated after the conductivities are intro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In our simulation for the case of finite conductivities, we take the values of conductivities as σ = 5.8 MeV and σ χ = 1.5 MeV same as Refs. [44,46]. Here we notify that σ = 5.8 MeV is consistent to the lattice QCD calculations at top temperature of QGP produced at RHIC and it is expected that the expansion of QGP causes the decrease in σ together with temperature of medium.…”
Section: Spatial Distributionssupporting
confidence: 88%
See 3 more Smart Citations
“…In our simulation for the case of finite conductivities, we take the values of conductivities as σ = 5.8 MeV and σ χ = 1.5 MeV same as Refs. [44,46]. Here we notify that σ = 5.8 MeV is consistent to the lattice QCD calculations at top temperature of QGP produced at RHIC and it is expected that the expansion of QGP causes the decrease in σ together with temperature of medium.…”
Section: Spatial Distributionssupporting
confidence: 88%
“…More details about broken symmetry of spatial distribution of the electric and magnetic fields are given in Refs. [44,46]. We have also checked the spatial distribution for Zr+Zr collisions at b = 7 fm at √ s N N = 200 GeV and found that the trends for both cases are similar to those in Ru+Ru collisions.…”
Section: Spatial Distributionsmentioning
confidence: 74%
See 2 more Smart Citations
“…While a qualitative agreement can be achieved between our model calculation with setup-2 of electromagnetic field and the experimental data, a more precise quantitative agreement would requires a much more dedicate calculation of the electromagnetic field. Recent studies [48,92] have shown that including electric and chiral magnetic conductivities can affect both the decay speed and the spatial symmetry of the electromagnetic field, which may also influence the azimuthal distribution of heavy quarks and their decay products. These will be incorporated in our model calculation in an upcoming effort.…”
Section: Discussionmentioning
confidence: 99%